Cognition and evaluation of architecture environments based on geometric contour references and aesthetic judgements - Carreiro, M.; Andrade, M. A. P.; Dias, M. S. (Proceedings of the 22nd International Conference of the Association for Computer-Aided Architectural Design Research in Asia, 2017)
This paper presents the outline and the achieved results of an experimental study developed to understand the differences on how close architecture spaces with distinct geometric characteristics at contour level, including rounded, curvilinear and sharp, rectilinear elements, are perceived and evaluated. In order to do so, eighteen virtual reality architecture spaces were evaluated by thirty-two test-subjects according to like/dislike aesthetic judgments. As expected, the tested subjects showed a higher level of preference for spaces with rounded, curvilinear contour elements. On another way, when the level of space curvature was high, considering the whole space surface and not only the contour of plan transitions, the level of preference decreased significantly. These results support the idea that rounded, curvilinear elements are interpreted as being more pleasant and preferred than sharp, rectilinear ones and create new knowledge on the how the levels of such preference are more accurate for moderate rather than radical curvature rates.